The effect of Covid-19 ‘stay home process’ on metabolism parameters in diabetes mellitus patients: A single center, cross-sectional study (Annals of Medical Research, 2022)
Aim: We aimed to investigate the impact of quarantine (stay home process) on laboratory parameters (fasting blood glucose, HbA1c), diet, exercise and medication compliance in patients with diabetes mellitus (DM) during the COVID -19 pandemic.Materials and Methods: This study included 93 diabetes mellitus patients, who presented to our outpatient clinic. Biochemical parameters (glucose, HbA1c, lipid profile), dietary and exercise compliance of the patients were evaluated before and after the three- month quarantine in Turkey. Frequency of blood glucose measurement, medication compliance, hypoglycemia/hyperglycemia, need for hospitalization, and whether patients had an infection were self-reported.Results: The mean age of the 93 patients included in the study was 56.70 ± 13.51 years. 55.9% (n = 52) of patients were female and 44.1% (n = 41) were male. 89.2% (n = 83) of participants were type 2 DM and 10.8% (n = 10) were type 1 DM. 82.8% (n = 53) of patients were aged between 18 and 64 years. It was found that 78.5% (n = 73) of patients had dietary compliance. We found that 41.9% (n =39) of the patients exercised at home, 53.8% (n = 50) took their medications regularly, and 43.0% (n = 40) checked their blood glucose daily. When biochemical values were compared before and after the study, a statistically significant decrease in fasting glucose (pre-post 141-121 mg/dl) (p=0.026) and body mass index (pre-post 32.00-31.86 kg/m2) (p=0.008) was observed. There was no statistically significant difference in HbA1c and lipid levels in our analysis.Conclusion: In this study, patients who adhered to their diet and monitored their blood glucose at home during quarantine had more stable blood glucose levels. In the future, prevention strategies should be considered for patients with chronic diseases during possible quarantines.
Keywords: COVID -19; diabetes mellitus; quarantine